a 2 − 1 a 3 − a 2 + a − 1
If a 2 − 4 a − 3 = 0 , then find the value of the above expression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a 2 − 1 a 3 − a 2 + a − 1 = ( a + 1 ) ( a − 1 ) a 2 ( a − 1 ) + 1 ( a − 1 ) = ( a + 1 ) ( a − 1 ) ( a 2 + 1 ) ( a − 1 ) = a + 1 a 2 + 1
Did the same way dude!!
We do Euclidien divisor for a^3-a²+a-1 /a-1 the we get this equality a^3-a²+a-1 = (a-1)(a²+1) then we divise it by (a-1)(a+1) after it we put a² =4a+3 the we simplify by a+1 then wo get 4 . thank you
if 4=4 so a = whatever Why I replace "Whatever" in equation not equal 0
a^2+1/a+1 next from eqoul 2 a^2+1=4(a+1)
The given expression can be simplified to a 2 − 1 ( a − 1 ) ( a 2 + 1 ) . . . . . . . . . . . . . . . . . . . . ( 1 ) .Now,we are also given that a 2 − 4 a − 3 = 0 ⟹ a 2 − 4 a − 4 + 1 = 0 ⟹ a 2 + 1 = 4 a + 4 = 4 ( a + 1 ) .Substituting in ( 1 ) gives a 2 − 1 ) 4 ( a + 1 ) ( a − 1 ) = a 2 − 1 4 ( a 2 − 1 ) = 4 .
a 2 − 4 a − 3 = 0 has roots a = 2 + 7 and a = 2 − 7
With Factor Theorem we have a − 1 as a factor of a 3 − a 2 + a − 1 and it can be factorised into ( a − 1 ) ( a 2 + 1 ) .
Hence
a 2 − 1 ( a − 1 ) ( a 2 + 1 ) = > a + 1 a 2 + 1
Both values of a give the value of the expression as 4 and we are done .
I tried doing it the same way but I didn't have any paper around XD. Not as elegant as the other way but it gets the job done
separating the common things equalize the equation and then after solving we get 4 the answer
My solution was much messier... I found the roots as square root of two + 7, and plugged it in.
Forgive any bad Latex coding I'm new to it but here's the solution....
Simplify both top and bottom of the equation giving us:
( a − 1 ) ( a + 1 ) ( a − 1 ) ( a 2 + 1 )
cancel out the a − 1 which then gives us:
a + 1 a 2 + 1
now using the information given in the question that a 2 − 4 a − 3 = 0 we look to the numerator...
a 2 + 1 = a 2 − 4 a + 4 a + 1 + 3 − 3
= a 2 − 4 a − 3 + 4 a + 4
= 0 + 4 a + 4
= 4 ( a + 1 )
putting the numerator and denominator back together:
( a + 1 ) 4 ( a + 1 ) = 4
a^2 - 4a - 3 = 0 implies that a^3 = 4a^2 + 3a.
So we substitute that into the expression to get
(3a^2 + 4a - 1)/(a^2 - 1)
It also implies that a^2 = 4a + 3 and 3a^2 = 12a + 9
Substituting both into the expression again, we get
(16a + 8)/(4a + 2) = 4.
[a (a^2 + 1) - (a^2 + 1)]/ (a^2 - 1) = [(a^2 + 1) (a - 1)]/ [(a + 1) (a - 1)]
= (a^2 + 1)/ (a + 1)
= 4 since (a^2 + 1) = 4 a + 4 = 4 (a + 1) as the quadratic equation given.
Problem Loading...
Note Loading...
Set Loading...
a 2 − 1 a 3 − a 2 + a − 1 = ( a − 1 ) ( a + 1 ) ( a 3 − 1 ) + ( − a 2 + a ) = ( a − 1 ) ( a + 1 ) ( a − 1 ) ( a 2 + a + 1 ) − a ( a − 1 ) = ( a − 1 ) ( a + 1 ) ( a 2 + 1 ) ( a − 1 ) = a + 1 a 2 + 1
Now from the given quadratic we get a 2 = 4 a + 3 Thus, a + 1 4 a + 3 + 1 = a + 1 4 ( a + 1 ) = 4